The basis and limits of physician authority: a reply to critics. Issue 3 (June 1995) - May, T
Abstract : This paper develops a model of the nurse/physician authority relationship presented in an earlier issue of this journal, and responds to criticisms raised against that model in commentaries on that article. Specifically, I examine the discrepancy which exists between medical knowledge and nursing education, and show this discrepancy to be a difference in type, not quality. The implication is that improvements in nursing education will not affect the authority relationship between physician and nurse. To affect this relationship the nature of nursing education must change.